2020
DOI: 10.1016/j.psychres.2020.113046
|View full text |Cite
|
Sign up to set email alerts
|

Danger in danger: Interpersonal violence during COVID-19 quarantine

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
359
0
45

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 427 publications
(416 citation statements)
references
References 13 publications
12
359
0
45
Order By: Relevance
“…The psychological effects of the COVID-19 outbreak are still emerging and beginning to be known [ 1 , 2 ]. Among them, the psychological effects of the crisis, social distancing and social isolation measures (i.e., restrictive lockdowns) on children and their families constitute a great challenge in the field [ 3 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The psychological effects of the COVID-19 outbreak are still emerging and beginning to be known [ 1 , 2 ]. Among them, the psychological effects of the crisis, social distancing and social isolation measures (i.e., restrictive lockdowns) on children and their families constitute a great challenge in the field [ 3 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…A nationwide survey in China showed that almost 35% of the population experienced significant psychological distress, and a variety of psychological problems—i.e., anxiety and depression—were triggered by the current crisis [ 1 ]. In Western countries, evidence of emotional harm was also found during the acute period of the pandemic [ 2 ]. In this regard, the study and protection of mental health during the pandemic crisis emerges as one of the most important challenges for science, policy makers and administrations [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Women belong to one of the most vulnerable communities to the COVID-19 pandemic [14][15][16][17][18]. While useful insights are available in the literature, there is a lack of evidence-based health solutions that can be applied to help women alleviate health issues they face amid COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidence shows that women are among the hardest hit populations during the pandemic [14][15][16][17][18], especially non-white racial or ethnic communities such as black and Hispanic women [19,20]. A preliminary literature review indicates that factors in uencing women's increased vulnerability to COVID-19 can be grouped into ve primary contributors: (1) pronounced exposure to COVID-19, (2) issues related to women's reproductive health, (3) elevated domestic violence, (4) increased mental health challenges, and (5) lack of access to healthcare services.…”
Section: Study Protocol Registration: Prospero Crd42020194003mentioning
confidence: 99%
See 1 more Smart Citation